Implementation of 21st Century Integrative Thematic Learning: Efforts to Form Entrepreneurship Students - Harahap, Nazmi Handayani; Zakaria, Abd Razak; Basri, Hasan (Educative: Jurnal Ilmiah Pendidikan, 2024)
This study aims to find out about the implementation of integrative thematic learning in 21st century learning as an effort to form entrepreneurship students. This research method is library research. Library research is research where the data or materials needed to complete the research come from the library either in the form of books, encyclopedias, dictionaries, journals, magazines and so on. The results of this study indicate that the implementation of Integrative Thematic learning in forming edupreneurship students can be done by: Integrated in all subjects, integrating with extracurricular activities, instilling a sense of responsibility, instilling in students to dare to take risks, instilling self-confidence in students towards their own abilities, instilling in students to have leadership skills, easily adapting to everyone, and being open to people's suggestions and criticisms, instilling in students to be able to be innovative, creative and flexible. The implications of implementing 21st century integrative thematic learning for entrepreneurship students are very important in current education. First, this approach allows the integration of various disciplines under one relevant theme, such as agriculture and fisheries, enriching students' learning experience and preparing them with a holistic understanding of entrepreneurship.